AN EVALUATION OF ACADEMIC INSTITUTIONAL REPOSITORIES IN GHANA - Kumah, Mariyama Abdulai; Filson, Christopher K. (International Journal of Knowledge Content Development & Technology, 2022)
Abstract Purpose- This study aims to evaluate some academic institutional repositories (IRs) in Ghana using the Evaluation Model of IR as parameters to determine their success. Design/ Methodology/ Approach- Data were collected using observation methods by examining the various web sites of seven (7) selected academic institutional repositories in Ghana. Findings- The findings revealed that the University of Ghana lead records count on the seven IRs examined. Dspace was the prioritized software for managing and preserving digital contents on these IRs. Theses and dissertations, research articles were the leading contents deposited on the IRs. Majority of the IRs have incorporated RSS feeds on their IR with few using other Web 2.0 features. English was the only interface language used on all the IRs. Research Limitations/ Implications- The main limitation of the study was that the findings were based on observation data collection on the various IRs webpage. Originality/ value- The study evaluated some academic IRs in Ghana and its impact on the institution’s visibility globally.